Test Accounts: A Hidden Risk. - Vachon, Phil (Communications of the ACM, 2025)
The article highlights the critical importance of safeguarding production environments and test accounts in computer software testing, emphasizing that even minor lapses can lead to significant risks such as data breaches, compliance violations, or reputational damage. It underscores best practices like enforcing strict access controls, implementing privileged access management (PAM), and maintaining robust telemetry to monitor and audit account usage. Additionally, the article cautions against shared credentials and impersonating customers, advocating instead for individual, tightly controlled test accounts that adhere to the principles of least privilege and accountability.